Seasonality in the manifestation of type 1 diabetes varies according to age at diagnosis in Finnish children - Turtinen Maaret; Härkönen Taina; Ilonen Jorma; Parkkola Anna; Knip Mikael; Finnish Pediatric Diabetes Register (WILEY, 2025)
Aim: We tested the hypothesis of a more aggressive disease process at diagnosis of type 1 diabetes during fall and winter, the colder seasons with consistently observed higher incidence of type 1 diabetes.
Methods: Seasonality in the manifestation of type 1 diabetes was examined in 4993 Finnish children and adolescents. Metabolic characteristics, beta-cell autoantibodies and HLA class II genetics were analysed at clinical diagnosis.
Results: Significant seasonality was observed with higher number of new cases during fall and winter (n = 1353/27.1% and n = 1286/25.8%) compared with spring and summer (n = 1135/22.7% and n = 219/24.4%) (p < 0.001). The youngest children (aged 0.5-4 years) differed from the older ones (aged 5-14 years) as a minority of them were diagnosed in winter (p = 0.019) while the older children followed the same pattern as that seen in the total series. Poorer metabolic decompensation was observed during seasons with lower number of new diagnoses.
Conclusion: The heterogeneity in the seasonality of diabetes manifestation between younger and older children suggests that different environmental factors may trigger the disease at different ages. Poorer clinical condition associated with seasons with a lower number of new cases may be more likely to be due to a delay in seeking medical help than to a more aggressive autoimmunity.